How (Im)Mobile Are Coworkers in Mid-Sized Cities? Comparing the Spatial Mobility Trajectories of Coworking Communities in Lille, Lyon and Rouen - Petani, Fabio; Chabanet, Didier; Richard, Damien (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
This paper studies the spatial mobility of around a thousand coworkers of three, mid-sized French cities to better understand coworking spaces. Our analysis, based on online available data on coworkers’ career and education trajectories, and confirmed by selected interviews with the founder, managers and users of the three coworking spaces, reveals a community with purposefully reduced mobility. We provide insights into how coworking spaces, by pooling a diversity of local resources, foster dynamism and allow a reduced spatial mobility option for a less kinetic elite of highly educated workers. Coworking spaces allow coworkers to develop entrepreneurial capabilities whilst striking a balance with their private life. The studied coworking community collectively achieves its goals, with individuals engaging in little international mobility and an overall reduced spatial mobility.